A Stereo Crosstalk Cancellation System Based on the Common-Acoustical Pole/Zero Model. (11th August 2010) - Wang, Lin; Yin, Fuliang; Chen, Zhe
Abstract : Crosstalk cancellation plays an important role in displaying binaural signals with loudspeakers. It aims to reproduce binaural signals at a listener's ears via inverting acoustic transfer paths. The crosstalk cancellation filter should be updated in real time according to the head position. This demands high computational efficiency for a crosstalk cancellation algorithm. To reduce the computational cost, this paper proposes a stereo crosstalk cancellation system based on common-acoustical pole/zero (CAPZ) models. Because CAPZ models share one set of common poles and process their zeros individually, the computational complexity of crosstalk cancellation is cut down dramatically. In the proposed method, the acoustic transfer paths from loudspeakers to ears are approximated with CAPZ models, then the crosstalk cancellation filter is designed based on the CAPZ transfer functions. Simulation results demonstrate that, compared to conventional methods, the proposed method can reduce computational cost with comparable crosstalk cancellation performance.